2011
DOI: 10.1002/jsfa.4682
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory activities of aqueous extract of Mesona procumbens in experimental mice

Abstract: Mesona procumbens has the potential to provide a therapeutic approach to inflammation-associated disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Chlorogenic acid was able to enhance the activity of the important antioxidant enzymes SOD, CAT and GSH-Px in STPZ-nicotinamide-induced type 2 diabetic rats [143]. Complementary studies reported that aqueous extract of Mesona procumbens , which has chlorogenic acid as a major compound, has anti-inflammatory action via the upregulation of antioxidants and downregulation of pro-inflammatory biomarkers (TNF-α, iNOS and COX-2) [144], and it exhibits anti-obesity effects and improves lipid metabolism [145]. …”
Section: Effects Of Bioactive Compounds From the Morinda Citrifolimentioning
confidence: 99%
“…Chlorogenic acid was able to enhance the activity of the important antioxidant enzymes SOD, CAT and GSH-Px in STPZ-nicotinamide-induced type 2 diabetic rats [143]. Complementary studies reported that aqueous extract of Mesona procumbens , which has chlorogenic acid as a major compound, has anti-inflammatory action via the upregulation of antioxidants and downregulation of pro-inflammatory biomarkers (TNF-α, iNOS and COX-2) [144], and it exhibits anti-obesity effects and improves lipid metabolism [145]. …”
Section: Effects Of Bioactive Compounds From the Morinda Citrifolimentioning
confidence: 99%
“…Mesona procumbens is a natural drink and is the main component of grass jelly in Taiwan (Huang et al, ). M. procumbens has therapeutic potential in the treatment of inflammation‐associated disorders (Huang et al, ). The inhibition of monosodium urate‐induced xanthine oxidase activity in human acute monocytic leukemia THP‐1 cells by a 50% ethanol extract of M. procumbens has been demonstrated (Jhang et al, ); this highlights the potential to improve hyperuricemia by the downregulation of xanthine oxidase activity in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Mesona procumbens is a natural drink and is the main component of grass jelly in Taiwan (Huang et al, 2012). M. procumbens has therapeutic potential in the treatment of inflammation-associated disorders (Huang et al, 2012).…”
mentioning
confidence: 99%
“…It also attenuates the gene expression of peroxisome proliferator-activated receptor-α in the regulation of liver function in rats (Ong, Hsu, & Tan, 2013;Wan et al, 2013) and contributes to the maintenance of the gastric epithelium in vitro (Bhatt, Rawat, Badhani, & Rawal, 2017). Other phenolic compounds identified in the current study have also been associated with important bioactive properties (Huang et al, 2012) showed that vanillic acid has antiinflammatory activity in mice and ferulic acid has activity in suppressing platelet aggregation (Arai et al, 2000;Yang et al, 2016) reported the consumption of flavonoids (such as myricetin) was inversely related to the total plasma cholesterol and the total concentration of low-density lipoprotein cholesterol in humans.…”
Section: Resultsmentioning
confidence: 62%